The Implementation of CPS Learning Assisted with Problem Cards on The Ability to Solve Story Problems (Universitas Negeri Semarang, 2019)
The purpose of this study is to obtain the ability of students in solving to solve story problems that fulfill learning (Creative Problem Solving) CPS assisted with problem cards is completely more than 75%, the ability to solve story problems that obtain CPS learning assisted with problem cards is better than classes that get learning using an example non-example type cooperative model, and to describe of the ability to solve student story problems. The type of research is quantitative descriptive with a quasi-experimental design. The research sample was all grade IV Public Elementary School Sekaran 01 Semarang. Data collection methods use tests and interviews. Quantitative analysis techniques include the completeness test and the average difference test. Finding shows that students who obtain learning with the CPS learning model assisted with the problem card media reach the ability to solve the story questions more than 75%, that is 90%, students who have the ability to solve story problems that obtain CPS learning by problem card media is better than students who obtain learning with the example-non-example type model, and students with the ability to solve high and medium criterion story problems are able to solve story problems with the four Polya steps, but students with the ability to complete medium criterion story problems have not yet written units, while students with the ability to solve low story criterion problems are still confused in distinguishing steps; plan, implement and recheck.